Validation of an obstetric fistula screening questionnaire: a case-control study with clinical examination - Chi Chiung Grace Chen; Annelise Long; Denis Rwabizi; Gerard Mbabazi; Ntwali Ndizeye; Blaise Dushimiyimana; Eugene Ngoga (BMC, 2022)
Plain language summary Obstetric fistula (OF) is a birth injury which may occur in women living in lower resource settings who experience obstructed labor (not progressing normally) without access to skilled obstetric care. This injury causes a woman to constantly leak urine and/or feces from her birth canal. As OF affects poor women who live far from healthcare it is difficult to fully understand how many women worldwide have an OF. Furthermore, although some Demographic and Health Surveys (DHS) include OF symptom questions, the accuracy of these questions in identifying women with OF has not been studied. To more accurately determine which women may have an OF, we developed an OF screening questionnaire after consulting OF experts worldwide, which included a DHS OF question. We asked women from Rwanda this questionnaire and then examined these women to see if they have OF. Through this process we identified 59 women with a LUTF, 34 with a LGTF, and 274 without an OF. The best performing questions were able to identify women with LUTF 100% of the time and women with LGTF 97% of the time. We also showed that one DHS question detects women with LUTF and LGTF 100% and 85% of the time, respectively. Public health officials can now use the questions we studied to more accurately estimate how many women worldwide have OF, and best direct resources and skilled health care workers to the areas with the greatest need.